EVALUATION OF THE SIGNIFICANCE OF TRANSVERSAL SKILLS IN EDUCATION FOR TEXTILES AND LEATHER SECTOR - Matković, Vesna Marija Potočić; Brnada, Snježana (PEOPLE: International Journal of Social Sciences, 2018)
Beside engineering skills related to textile, clothing, leather and footwear (TCLF) technology all recent reports from European organizations highlight the importance of introduction of transversal skills into educational programs. This research comprises the opinions of 66 Croatian employers from TCLF sector related to ranking of importance of transversal skills. Social and civic skills, cultural awareness and creative expression, ability to respect diversity and communication skills are more sought after in design related jobs. Psychomotor skills, reaction time, precision of machine and equipment control are highly rated for engineering jobs. Engineers also need skills in the field of human resources management, empathy, analytical and organizational skills, resource management; customer needs targeting and focus on results.